Simulation analysis of livestock production efficiency and its impact on women’s empowerment in Bangladesh: Livestock, Efficiency, and Women's Empowerment - Roy, Rajib Kumar; Sarma, Paresh Kumar; Khan, Jahangir Alam; Haque, Sadika; Ahmed, Jasim Uddin (Journal of the Sylhet Agricultural University, 2026)
Livestock production plays a vital role in rural livelihoods and household security in Bangladesh, yet gender disparities often limit women’s participation and decision making in this sector. This study investigates the relationship between livestock production efficiency and women’s empowerment among beneficiaries of the Livestock Development and Dairy Production (LDDP) project in Bangladesh. The main objective was to examine how women’s empowerment influence by technical efficiency in livestock production. Primary data were collected from 450 livestock-farming household across six upazilas in the LDDP coverage three southern divisions. Descriptive and inferential statistics, the Alkire–Foster methodology, stochastic frontier analysis (SFA), and ordered probit regression were applied to analyze the data. Results showed that the overall WELI score was 0.735, with 26.65% of women (WELI ≥ 0.80) classified as empowered. The mean TE scores were 0.941 for male-headed and 0.940 for female-headed households, respectively. A positive and statistically significant (p < 0.05) relationship between TE and WELI was observed, indicating that households with greater gender parity exhibit higher production efficiency. The study concludes that enhancing livestock production not only women empowers them but also improve overall productivity, supporting Sustainable Development Goals (SDGs) on gender equality and inclusive economic growth. Future research should explore longitudinal impacts and the role of institutional support in sustaining women’s empowerment in livestock farming. J. Sylhet Agril. Univ. 12(2): 33-46, 2025